1986
DOI: 10.1128/iai.53.2.404-410.1986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perorally administered lactobacilli on macrophage activation in mice

Abstract: The effect of perorally (p.o.) administered Lactobacillus casei and L. bulgaricus on macrophage activation in mice was studied. L. casei and L. bulgaricus were administered p.o. to mice for 8 days. The macrophage activation was measured on days 2, 3, 5, and 8 of lactobacillus administration by using biochemical and functional criteria. We measured the release of lysosomal hydrolases, the level of a nonlysosomal enzyme, and in vitro phagocytic activity of mouse peritoneal macrophages. All the assays were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
5

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(74 citation statements)
references
References 16 publications
0
68
1
5
Order By: Relevance
“…In this study, we demonstrated that murine M~b produce IFN when exposed to some strains of heat-killed L. gasseri. Both live and killed lactic acid bacteria exhibit biological activity [16][17][18][19]. We found that live L. gasseri DSM20243 T also induced IFN production (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we demonstrated that murine M~b produce IFN when exposed to some strains of heat-killed L. gasseri. Both live and killed lactic acid bacteria exhibit biological activity [16][17][18][19]. We found that live L. gasseri DSM20243 T also induced IFN production (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Probiotic bacteria have been used extensively within the food industry, largely in fermented milk products. Claims of probiotic promotion of host defence have been supported by reports of enhanced phagocytosis [12,13], stimulation of production of various cytokines (including IL-2, IL-4, IL-10, IL-12, IL-18 and INF-g ) [14][15][16][17][18][19] and increased mucosal and secretory antibody levels in response to gut infection with rotavirus [20][21][22] or Salmonella typhi Ty21a [20,23], supporting the notion that some probiotics can enhance mucosal immunity. Feeding adult or neonatal nude mice probiotics prolonged their survival following intestinal challenge with live C. albicans by enhancing both antibody and cell-mediated immunity [24,25].…”
Section: Introductionmentioning
confidence: 97%
“…This was reinforced by experiments eval- uated at the ultra structural level, using electron microscopy [22]. The mechanisms suggested in the protective e¡ect of probiotic microorganisms [16] are very broad: from competitive exclusion [17], nutrient competition [31], production of antagonistic substances (lactic acid, hydrogen peroxide [32], bacteriocins [33]) up to immune system stimulation [14,15]. From the results obtained in the present paper, it can be suggested that the intervention of the immune system could be involved as one of the main mechanisms responsible for the protective e¡ect exerted on S. pneumoniae infection and is based on the following grounds:…”
Section: Discussionmentioning
confidence: 99%